LEGAL PROTECTION OF INTELLECTUAL PROPERTY - G.B. Bagytzhan; J.Zh. Zhagypar; E.I. Kukkuzova (Academic Journal of Physical and Chemical Sciences, 2019)
Intellectual property is the result of only the mental activity of man. The subjects of the rights of this property can be both citizens (authors), including individual entrepreneurs, and legal entities - organizations. This often leads to conflict situations between creators and legal entities claiming to be the owners of the results of intellectual activity of the creator. Intellectual property is inherently new information and is valued, can be used simultaneously by an unlimited number of people, it is difficult to limit the territory of their use. However, crimes in the field of intellectual property often constitute an infringement of the author’s rights without his consent, as described in detail by the authors of this article.